2011
DOI: 10.1589/jpts.23.821
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Exercise by Chronic Stroke Patients in Aquatic and Land Environments

Abstract: The purpose of this study was to compare the effects of land exercise and aquatic exercise on chronic stroke patients. [Subjects and Methods] The subjects were randomly divided into a land exercise group (12 males and 10 females; average age: 56.09 ± 7.22 years) and an aquatic exercise group (15 males and 7 females; average age: 51.55 ± 8.27 years). Subjects from both groups received general conventional treatment during the experimental period. In addition, all subjects engaged in extra treatment sessions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…Recently there has been a rise in the interest in the usefulness of exercises in water for the rehabilitation of post-CVA patients. Most studies comparing the effectiveness of balance training in the water and in a gym showed that better results were achieved during balance training in water [54,[60][61][62][63].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently there has been a rise in the interest in the usefulness of exercises in water for the rehabilitation of post-CVA patients. Most studies comparing the effectiveness of balance training in the water and in a gym showed that better results were achieved during balance training in water [54,[60][61][62][63].…”
mentioning
confidence: 99%
“…Meanwhile, when exercising in water, its physical characteristics (hydrostatic pressure, the lift force, and high density) reduce the patients' fear of falls and injuries [60,61]. Water has a specific mechanical effect on the body, reducing pain, peripheral edemas, the activity of the sympathetic nervous system, and biomechanical muscle and joint tension, and improving proprioception, which creates better conditions for rehabilitation [60,63] The results of the studies conducted by Kog Noh et al, Han et al, Lee et al, and Jung et al evaluating the effectiveness of balance training in water and in a gym showed that balance training in water was more effective, and the difference, compared to balance training in a gym, was statistically significant [54,60,62,63].…”
mentioning
confidence: 99%
“…As a result, the change in balance ability led to improvement of walking ability. This change is due to the advantage of the water environment, which reduces the stress on the joints through buoyancy, which counteracts the gravity felt by the human body on the ground, enabling movement with less force compared with the ground motion [27,28]. It is reported that such underwater gait training im-proves balance ability by increasing the stance phase and weight transfer ability of the affected side [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Based on the results of Masumoto et al 11 we found that the application of underwater treadmill was the basis for a positive change in lower extremity muscle activity. In particular, Park et al 12 JaeHoPark,etal. 15 found that the stability of the lower extremity increases with the application of aquatic treadmill through three-dimensional motion analysis.…”
Section: Introductionmentioning
confidence: 99%